ЎЗБЕКИСТОННИНГ ШИМОЛИ - ҒАРБИЙ ҲУДУДЛАРИДА ТАРҚАЛГАН ВИЗИЛДОҚ ҚЎНҒИЗЛАРИГА(COLOEPTERA: CARABIDAE) АНТРОПОГЕН ОМИЛЛАР ТАЪСИРИНИ ЭКОЛОГИК БАҲОЛАШ - Реймов, Қ.Д.; Ешмуратов, А.Я.; Гулимбетов, Б.Д.; Сейтмуратов, А.Қ. (SCIENCE and SOCIETY, 2021)
The article presents the ecological characteristics of 104 ground beetle species belonging to 39 genera of 7 subfamilies common in the North-West of Uzbekistan, based on the results of scientific research conducted in 2018-2021.